2008
DOI: 10.1096/fj.08-120006
|View full text |Cite
|
Sign up to set email alerts
|

Duox maturation factors form cell surface complexes with Duox affecting the specificity of reactive oxygen species generation

Abstract: Dual oxidases (Duox1 and Duox2) are plasma membrane-targeted hydrogen peroxide generators that support extracellular hemoperoxidases. Duox activator 2 (Duoxa2), initially described as an endoplasmic reticulum resident protein, functions as a maturation factor needed to deliver active Duox2 to the cell surface. However, less is known about the Duox1/Duoxa1 homologues. We identified four alternatively spliced Duoxa1 variants and explored their roles in Duox subcellular targeting and reconstitution. Duox1 and Duo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
171
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(180 citation statements)
references
References 39 publications
6
171
0
2
Order By: Relevance
“…The DUOX1/ DUOXA1 genes are aligned head-to-head in a compressed genomic locus on chromosome 15, suggesting that expression of DUOX1 oxidase and its maturation factor are coordinated by a common bidirectional promoter (14). Several alternative splicing variants of DUOXA1 mRNA have been identified, and the lack of coding exon 6 has been shown to generate inactive forms of DUOXA1 (15).…”
Section: Resultsmentioning
confidence: 99%
“…The DUOX1/ DUOXA1 genes are aligned head-to-head in a compressed genomic locus on chromosome 15, suggesting that expression of DUOX1 oxidase and its maturation factor are coordinated by a common bidirectional promoter (14). Several alternative splicing variants of DUOXA1 mRNA have been identified, and the lack of coding exon 6 has been shown to generate inactive forms of DUOXA1 (15).…”
Section: Resultsmentioning
confidence: 99%
“…The H 2 O 2 production by DUOX2 requires a maturation factor (DUOXA2) that is co-expressed with DUOX2 and permits the translocation of DUOX2 from the endoplasmic reticulum to the Golgi apparatus, and its subsequent maturation and translocation to the apical membrane. Recent studies revealed that the expression of Duox2 mRNA is rapidly stimulated by TSH through the cAMP pathway in human, porcine, canine, and FRTL-5 cells (1,4,23,50).…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 is produced by two isoform enzymes, DUOX1 and DUOX2, which were initially identified in the thyroid as nicotinamide adenine dinucleotide phosphate (NADPH) oxidases (NOX) that produce H 2 O 2 , either by direct generation or through the production of O 2 -as a precursor (1)(2)(3)(4). The activities of NOX/DUOX are regulated at the level of enzyme assembly.…”
mentioning
confidence: 99%
“…This suggests that DUOX1 may be active in lung tissue but requires other protein interactions for maturation (DUOXA1), transport, or activity (59,60). Recently, the DUOX maturation factors (DUOXA1 and DUOXA2) were shown to form stable cell surface complexes with the DUOX proteins and may function as part of a H 2 O 2 -generating enzyme complex (61). Co-expression of hDUOX1 in the presence of DUOXA1 or pull-down assays of the peroxidase domain with mammalian cell lysates may provide a better understanding of any specific protein interactions that modulate DUOX1 activity.…”
Section: Discussionmentioning
confidence: 99%